Thyroid-Associated Ophthalmopathy after Radioactive Iodine Therapy for Metastatic Follicular Thyroid Carcinoma - Daisuke Murayama; Soji Toda; Yoichiro Okubo; Hiroyuki Hayashi; Ai Matsui; Mio Yasukawa; Hiroyuki Iwasaki (Case Reports in Endocrinology)
Thyroid-associated ophthalmopathy (TAO) is an inflammation of the extraocular muscles and periorbital connective tissue caused by autoantibodies against common antigens to both the thyroid and orbit. The release of antigens and induction of hypothyroidism caused by radioactive iodine (RAI) therapy may exacerbate TAO. Here, we present the case of a 67-year-old-woman treated with RAI therapy for metastatic follicular thyroid carcinoma who presented with TAO during the course of sorafenib administration. Tg and TgAb levels were gradually decreased with sorafenib and lenvatinib treatment, and TAO was improved without any ophthalmologic treatment.